COMPOSITION OF UNDER-SHRUBS SPECIES IN MOUNT SALAK NATIONAL PARK, WEST JAVA - Inge Larashati (JURNAL PENELITIAN BIOLOGI BERKALA PENELITIAN HAYATI, 2011)
Forest in Mount Salak area has a very important existence, so that in the year of 2003 was announced officially as a conservation area and became a part of Mount Halimun Salak National Park (TNGHS). As one of the conservation area in Indonesia, Mount Salak forest has so many natural resources which support the living prosperity of the people, especially The West Java citizen. But in the use of the natural resources people have never been appreciating the conservation concepts then causing the forest degradation rapidly and terribly saddening. In order to explore the vegetation in the conservation area left, then the ecology analysis was done by making research plots in a hectare area. Data collecting was done on the systematically-located 1 meter square-size sub-plots. Those plots were located in a relatively-good natural forest. Data analysis result stated Athyrium dilalatum, Stenochlaena palustris, Calamus javensis, Curculigo latifolia and Strobilanthes blumei were the species which dominated Mount Salak National Park in the altitude of 1.267 meter above sea level.